Patients with rheumatoid arthritis and osteoarthritis in terms of sex hormone receptors and histopathological comparison of features - Turgut KÜLTÜR; Mehmet ZENGİN (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the relationship between estrogen receptors (ERs) and progesterone receptors (PRs) and histopathological findings in synovial tissue in rheumatoid arthritis (RA) and osteoarthritis (OA) patients. Patients and methods: Synovial tissue samples obtained from synovial surgery from 30 RA (10 males, 20 females) and 92 OA (27 males, 65 females) patients with median age of 59 (range, 50 to 67) years were analyzed retrospectively between January 2010 and January 2019. The relationship between histopathological features and hormone receptor presence was analyzed. Results: There was a meaningful relationship between histopathological parameters and RA and OA (p=0.01). The sex hormone receptor’s presence was significantly higher in females with RA (p=0.01). Additionally, in the RA group, there was a remarkable relationship between ER and focal aggregates of lymphocytes (p=0.01), perivascular infiltrates of lymphocytes (p=0.03), and diffuse infiltrates of lymphocytes (p=0.01). In the OA group, a significant relationship was observed between PR and subchondral inflammation (p=0.01). In multivariate analysis, it was observed that ER was an independent risk factor for focal aggregates of lymphocytes in RA group (odds ratio [OR]=1.51 [1.02-2.25], p=0.04). Besides, PR was found to be an independent risk factor for subchondral inflammation in OA group (OR=3.90 [1.28-11.80], p=0.02). Conclusion: The presence of the sex hormone receptor in the synovium may change histopathological features and affect the clinical course.